2007
DOI: 10.1021/la700883y
|View full text |Cite
|
Sign up to set email alerts
|

Methylene Blue-Containing Silica-Coated Magnetic Particles:  A Potential Magnetic Carrier for Photodynamic Therapy

Abstract: We present the preparation and characterization of methylene blue-containing silica-coated magnetic particles. The entrapment of methylene blue (MB), a photodynamic therapy drug under study in our group, in the silica matrix took place during the growth of a silica layer over a magnetic core composed of magnetite nanoparticles. The resulting material was characterized by transmission electron microscopy (TEM), light scattering, and X-ray diffraction. It is composed of approximately 30 nm silica spheres contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
134
0
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(147 citation statements)
references
References 51 publications
5
134
0
8
Order By: Relevance
“…In recent years, with the advancement of nanotechnology, engineered nanoparticles have received attention as a possible means of encapsulating and delivering PDT agents. Research in our laboratories [17][18][19][20][21][22] and elsewhere [23,24] has demonstrated the utility of nano-structured materials, which employ biocompatible nanoparticle matrices encapsulated with efficient photo-active molecules, for PDT. Our concept of a nanoparticle platform (NP) was initiated by the design of Photonic Explorers for Biomedical use by Biologically Localized Embedding, termed PEBBLEs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the advancement of nanotechnology, engineered nanoparticles have received attention as a possible means of encapsulating and delivering PDT agents. Research in our laboratories [17][18][19][20][21][22] and elsewhere [23,24] has demonstrated the utility of nano-structured materials, which employ biocompatible nanoparticle matrices encapsulated with efficient photo-active molecules, for PDT. Our concept of a nanoparticle platform (NP) was initiated by the design of Photonic Explorers for Biomedical use by Biologically Localized Embedding, termed PEBBLEs.…”
Section: Introductionmentioning
confidence: 99%
“…The intensities of absorption at 456 nm were plotted against irradiation time. The singlet oxygen quantum yield (η) of SPPLGA in DMF was calculated using following equation [23]:…”
Section: Singlet Oxygen Production Measurementmentioning
confidence: 99%
“…DPBF is a singlet oxygen quencher which can qualitatively establish the production of singlet oxygen, which result in a decreased intensity of the DPBF fluorescence band at 414 nm. According to the reported singlet oxygen generation estimation method, The singlet oxygen quantum yield (η) of polymer were evaluated by comparison with those obtained in previous work for 5,10,15,20-tetraphenylporphyrin (TPP) (0.67±0.09) [23]. In Fig.…”
Section: Singlet Oxygen Production Measurementmentioning
confidence: 99%
“…The samples were analyzed by transmission electron microscopy (TEM), which revealed particles in the range of 30-40 nm, with predominance of aggregates in a pearl necklace-like-structure. The material, so obtained, was used in applications that included immobilizing of drugs for biomedical applications, 49 as well as catalysts for magnetic separation. 50 Because it requires high dilution of the coating solution, this method limits the amount of material obtained to hundreds of milligrams in each reaction.…”
Section: Coating Magnetite With Silicamentioning
confidence: 99%